Online Cutomer Review dan Online Custoemer Rating : Loyalitas Konsumen Gen Z pada E-Commerce Shoppe di Kota Medan - Roma Agnesia Pasaribu; Hendrik Putra Lombu; Bayu Teta (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the influence of Online Customer Review and Online Customer Rating on the Loyalty of Gen Z consumers on the Shopee e-commerce platform in Medan City. The research method used is quantitative with a sample size of 55 respondents. Data were analyzed using multiple linear regression with the assistance of SPSS version 26. Validity and reliability tests indicated that the research instruments were valid and reliable. Classical assumption tests, including normality, multicollinearity, and heteroscedasticity, were met. The regression analysis results showed that Online Customer Review and Online Customer Rating have a positive and significant effect on Consumer Loyalty, both partially and simultaneously. The Adjusted R Square value of 0.263 indicates that these two variables explain 26.3% of the variation in consumer loyalty.